2012
DOI: 10.1128/aem.02304-12
|View full text |Cite
|
Sign up to set email alerts
|

3′ Untranslated Region-Dependent Degradation of the aceA mRNA, Encoding the Glyoxylate Cycle Enzyme Isocitrate Lyase, by RNase E/G in Corynebacterium glutamicum

Abstract: We previously reported that the Corynebacterium glutamicum RNase E/G encoded by the rneG gene (NCgl2281) is required for the 5= maturation of 5S rRNA. In the search for the intracellular target RNAs of RNase E/G other than the 5S rRNA precursor, we detected that the amount of isocitrate lyase, an enzyme of the glyoxylate cycle, increased in rneG knockout mutant cells grown on sodium acetate as the sole carbon source. Rifampin chase experiments showed that the half-life of the aceA mRNA was about 4 times longer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 47 publications
4
43
0
Order By: Relevance
“…aureus and S . enteric (Maeda and Wachi, ; Ruiz de los Mozos et al ., ; Lopez‐Garrido et al ., ). The work reported here reveals that the 3 ′ UTR of hmsT mRNA is a negative modulator of hmsT mRNA in Y. pestis .…”
Section: Discussionmentioning
confidence: 99%
“…aureus and S . enteric (Maeda and Wachi, ; Ruiz de los Mozos et al ., ; Lopez‐Garrido et al ., ). The work reported here reveals that the 3 ′ UTR of hmsT mRNA is a negative modulator of hmsT mRNA in Y. pestis .…”
Section: Discussionmentioning
confidence: 99%
“…Similar observations were reported that several E. coli mRNAs, such as those of the betT , mltD and bdm genes, are subjected to RNase III cleavage in their coding region (Sim et al ., ; Lim et al ., ; Sim et al ., ). In the case of C. glutamicum , the degradation of aceA mRNA by RNase E/G is 3′‐UTR dependent (Maeda and Wachi, ). In C. glutamicum , many mRNAs (33%) were identified to be leaderless mRNAs (Pfeifer‐Sancar et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…C. glutamicum has one RNase E/G ortholog and one RNase J ortholog, but no RNase Y (Maeda and Wachi, 2012b). Our previous study showed that RNase E/G is involved in the regulation of glyoxylate cycle and FMN riboswitch in C. glutamicum (Maeda and Wachi, 2012a;Takemoto et al, 2015). Therefore, it is possible that RNase E/G and/or RNase J play a central role in mRNA metabolism in C. glutamicum.…”
Section: Discussionmentioning
confidence: 99%
“…Results of this study indicate a control of the aceBA -operon of B. licheniformis in B. subtilis at the transcriptional level . A transcriptional regulation of the glyoxylate shunt has also been shown for the Gram-positive bacterium Corynebacterium glutamicum , where the expression of the malate synthase and isocitrate lyase is positively controlled by the LuxR-type transcriptional regulator RamA in the presence of acetate [15]. Voigt et al detected a strong induction of the AceB expression in B. licheniformis at the transcriptional and translational level as soon as the preferred carbon and energy source glucose is exhausted [16].…”
Section: Discussionmentioning
confidence: 99%